2017
DOI: 10.1021/acs.jafc.7b02956
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Bioactive Compound in Electrospun Fibers and Its Potential Application

Abstract: Electrospinning is a simple and versatile encapsulation technology. Since electrospinning does not involve severe conditions of temperature or pressure or the use of harsh chemicals, it has great potential for effectively entrapping and delivering bioactive compounds. Recently, electrospinning has been used in the food industry to encapsulate bioactive compounds into different biopolymers (carbohydrates and proteins), protecting them from adverse environmental conditions, maintaining the health-promoting prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(96 citation statements)
references
References 210 publications
0
84
0
Order By: Relevance
“…Several typical functions are oil-holding capacity, water-holding capacity, and antioxidative activity. 6 Wen et al 7 found that the oil-holding capacity of FPH was influenced heavily by molecular weight (MW) distributions and different processing methods. Furthermore, they compared oil-holding capacities of different 3256 www.soci.org Q Zeng et al…”
Section: Introductionmentioning
confidence: 99%
“…Several typical functions are oil-holding capacity, water-holding capacity, and antioxidative activity. 6 Wen et al 7 found that the oil-holding capacity of FPH was influenced heavily by molecular weight (MW) distributions and different processing methods. Furthermore, they compared oil-holding capacities of different 3256 www.soci.org Q Zeng et al…”
Section: Introductionmentioning
confidence: 99%
“…The morphology and size of the encapsulation structures can be adjusted by changing the process parameters. Moreover, the stability and functionality of bioactive compounds encapsulated in electrospun fibers may be enhanced at different relative humidity and temperature conditions (Wen et al., ).…”
Section: Functionalization Of Nanofibers For Active Food Packagingmentioning
confidence: 99%
“…The electrospinning of bioactive polymers including naturally occurring polymers, synthetic polymers, and polymer blends was well discussed, and the functionalization of the electrospun surfaces by incorporation of bioactive substances was proposed. Wen, Wen, Zong, Linhardt, and Wu () reviewed the encapsulation of bioactive compounds in electrospun nanofibers for potential food applications. The principles of emulsion electrospinning and coaxial electrospinning, and the used natural biopolymers (polysaccharides and proteins) were summarized to provide new strategies to develop novel functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several attempts at combining biomaterial scaffolds with controlled-release systems for specific applications [74]. Some approaches have simply utilized the addition of payloads to polymers prior to electrospinning, while others have used polymeric microspheres for encapsulation that are admixed with polymers prior to electrospinning [78,79,80]. The payloads in these approaches have varied from growth factors to small molecules (drugs) that have specific clinical applications (Figure 4).…”
Section: Electrospinning To Generate Nanofiber Scaffoldsmentioning
confidence: 99%